Procesos del pensamiento en la didáctica de la física - Abril, Sonia Adriana; Villamarin, Sonia Julieth (Góndola, enseñanza y aprendizaje de las ciencias, 2008)
In this article we make an approximation to the definition of didactics of physics from a perspective that analyses contents and thought processes immersed in apprentices. Didactics of physics is a science that studies why, how and for what is taught physics, from studies on relationship between physics and mathematics, knowledge construction, and relationships between physics, society and technology. The developments that occur in each aspect facilitate comprehension of nature in terms of abstraction and mathematization.